Significant Biologically Mediated CO2 Uptake in the Pacific Arctic During the Late Open Water Season. Issue 2 (1st February 2019) - Juranek, L.; Takahashi, T.; Mathis, J.; Pickart, R.
Abstract: Shifting baselines in the Arctic atmosphere‐sea ice‐ocean system have significant potential to alter biogeochemical cycling and ecosystem dynamics. In particular, the impact of increased open water duration on lower trophic level productivity and biological CO2 sequestration is poorly understood. Using high‐resolution observations of surface seawater dissolved O2 /Ar and p CO2 collected in the Pacific Arctic in October 2011 and 2012, we evaluate spatial variability in biological metabolic status (autotrophy vs heterotrophy) as constrained by O2 /Ar saturation ( ∆O 2 / Ar ) as well as the relationship between net biological production and the sea‐air gradient of p CO2 ( ∆pCO 2 ). We find a robust relationship between ∆pCO 2 and ∆O 2 / Ar (correlation coefficient of −0.74 and −0.61 for 2011 and 2012, respectively), which suggests that biological production in the late open water season is an important determinant of the air‐sea CO2 gradient at a timeframe of maximal ocean uptake for CO2 in this region. Patchiness in biological production as indicated by ∆O 2 / Ar suggests spatially variable nutrient supply mechanisms supporting late season growth amidst a generally strongly stratified and nutrient‐limited condition. Plain Language Summary: The Arctic is experiencing rapid change. One of the most notable changes is an increase in the length of time coastal areas of the Arctic are ice‐free in summer, which may affect the growth patterns of microscopic marine plants at the bottom of the food chain in Arctic ecosystems. We investigate how the growth at the base of the food chain is responding to these sea ice changes in the late, "open water" period. To track growth, we measure the oxygen content of the surface ocean, which constrains the balance of growth and loss as marine plants photosynthesize and then are consumed and decomposed. We also relate the spatial patterns of net growth to the amount of carbon dioxide (CO2 ) gas dissolved in the surface ocean to evaluate the potential impact of biological activity on the uptake of this important greenhouse gas into the surface ocean. We find a surprising relationship between growth and areas of CO2 uptake by the ocean. This finding is important because it suggests that the biological community facilitates carbon dioxide uptake during a timeframe when previously growth would be inhibited by ice cover. Key Points: We evaluate biological carbon cycling in the Pacific Arctic during the late open water season ∆O 2 / Ar and Δ pCO 2 observations suggest an important role for late season biological activity toward maintaining an ocean carbon sink High mesoscale variability in biological metabolism inferred from O2 /Ar suggests localized and likely episodic nutrient supply